To decompose the polynomial \( (x^2 - 5x + 6)(x^2 + 4x - 12) \) into linear factors, we can start by factoring each quadratic expression separately.
First, let's factor \( x^2 - 5x + 6 \): \[ x^2 - 5x + 6 = (x - 2)(x - 3) \] This is because the roots are \( x = 2 \) and \( x = 3 \).
Next, let's factor \( x^2 + 4x - 12 \): \[ x^2 + 4x - 12 = (x + 6)(x - 2) \] This is because the roots are \( x = -6 \) and \( x = 2 \).
Now we have: \[ (x^2 - 5x + 6)(x^2 + 4x - 12) = (x - 2)(x - 3)(x + 6)(x - 2) \] Notice that \( (x - 2) \) appears twice.
Combining all the factors, we get: \[ (x - 2)^2 (x - 3)(x + 6) \] Now we can match this with the given options:
- \( (x - 2)^2 (x - 3)(x + 2) \)
- \( (x - 1)(x - 6)(x + 2)(x - 2) \)
- \( (x - 2)^2 (x - 3)(x + 6) \)
- \( (x - 2)(x - 3)(x + 2)(x - 6) \)
The correct factorization is: 3) \( (x - 2)^2 (x - 3)(x + 6) \).